Acute and repetitive human exposure to isobutane. - Stewart, Richard D; Herrmann, Anthony A; Baretta, Edward D; Forster, Hubert V; Sikora, Jeanne J; Newton, Paul E; Soto, Ricardo J (Scandinavian Journal of Work, Environment & Health, 1977)
Eight adult volunteers of both sexes were exposed to isobutane in a controlled-environment chamber for the purpose of monitoring their physiological responses to a series of gas concentrations ranging from 250 to 1,000 ppm. First, the response to exposure periods of 1 min, 2 min, 1 h, 2 h, and 8 h were studied. There being no untoward responses to these acute exposures, the eight volunteers were exposed repetitively to isobutane at concentrations of 500 ppm, 1, 2 or 8 h per day, five days per week for two weeks. Then exposures to two mixtures of isobutane and propane for 1, 2 or 8 h per day for two days were studied. During the investigation all subjects were kept under comprehensive medical surveillance. No untoward subjective responses or abnormal physiological responses occurred during or following these exposures. Special emphasis was placed on evaluating the cardiac and pulmonary response to these exposures through the use of continuous ECG telemetry and serial computerized spirometric measurements. The following serial laboratory studies were unaltered by the exposures: complete blood count, urinalysis, serum alkaline phosphatase, SGOT, LDH, serum bilirubin, blood sugar, serum calcium, serum phosphorus, BUN, spontaneous electroencephalogram, visual evoked response, a battery of cognitive tests, and an ACTH stimulation test.
Keywords: acute human exposure; human response; isobutane; isobutane inhalation; repetition; repetitive human exposure